KEKUATAN PARTAI POLITIK ISLAM DALAM PEMILU LEGISLATIF 2024 PROVINSI JAWA BARAT (Studi Kasus Partai Persatuan Pembangunan) - Rochaeni, Atik; Fujilestari, Noer Apptika; Risyah Aprimayanti (Moderat : Jurnal Ilmiah Ilmu Pemerintahan, 2025)
This study aims to examine the strength of the United Development Party (Partai Persatuan Pembangunan/PPP) in the 2024 Legislative Election in West Java, the most populous province in Indonesia (48.7 million people) and a national political barometer. The research focuses on PPP’s resilience as an Islamic party in facing challenges such as the fragmentation of Muslim votes due to the emergence of new parties like the Ummat Party, shifts in young voters’ preferences (56.7% under the age of 40), and the dominance of economic–inflation issues, which are the top priority for 62% of voters. Employing a qualitative approach with a case study method, the study uses the theoretical framework of political capital to map PPP’s strategies, rooted in traditionalism and the pesantren (Islamic boarding school) network. The data was obtained from the results of in-depth interviews with a number of PPP cadres, administrators, and sympathizers who were actively involved in the political process at the local level. The findings indicate that institutional capital and social capital are the key factors enabling PPP to maintain its existence amidst competition from other Islamic parties. The pesantren network serves as a solid and consistent voter base supporting PPP’s victory in the 2024 Legislative Election in West Java.